2020
DOI: 10.1101/2020.12.28.424622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscapes and dynamic diversifications of B-cell receptor repertoires in COVID-19 patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the pandemic of coronavirus disease 2019 (COVID-19). Great international efforts have been put into the development of prophylactic vaccines and neutralizing antibodies. However, the knowledge about the B cell immune response induced by the SARS-CoV-2 virus is still limited. Here, we report a comprehensive characterization of the dynamics of immunoglobin heavy chain (IGH) repertoire in COVID-19 patients. By using next-generation sequencing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…To be able to analyze individual maturation trajectories of B cells in the primary vaccination series versus upon third vaccination, we set out to identify developmental B lineages in all individual participants and to track them across the vaccination period. A B cell lineage is a group of clonotype-defined B cells that share a common V and J gene and a CDR3 sequence differing only in up to 10% of its amino acid positions (35). While we did not detect expanding B cell lineages in a substantial proportion of participants receiving their primary vaccination series, we found expanding lineages in the majority of patients receiving their third vaccination (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to analyze individual maturation trajectories of B cells in the primary vaccination series versus upon third vaccination, we set out to identify developmental B lineages in all individual participants and to track them across the vaccination period. A B cell lineage is a group of clonotype-defined B cells that share a common V and J gene and a CDR3 sequence differing only in up to 10% of its amino acid positions (35). While we did not detect expanding B cell lineages in a substantial proportion of participants receiving their primary vaccination series, we found expanding lineages in the majority of patients receiving their third vaccination (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…We identified overlapping B cell lineages in the pre- and post-vaccination time point per patient. A B cell lineage was defined as a group of B cell clonotypes that share a common V and J gene and a CDR3 sequence differing only in up to 10% of its amino acid positions (35). Lineages and their evolution were visualised as stream plots with function plot.stacked from (https://www.r-bloggers.com/2013/12/data-mountains-and-streams-stacked-area-plots-in-r/).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, the clonotypes found to be enriched/to bear similarity to CoV-AbDab antibodies post SARS-CoV-2 exposure often differ across studies (20)(21)(22). This may be partly due to the small sample sizes used in individual studies, and the intrinsic biases in individual VJ gene usage; Xiang et al found a larger variation between individuals within a cohort (healthy, or three different severities of COVID symptoms) than between cohorts (22). Another contributing factor is lineage clustering itself.…”
Section: Introductionmentioning
confidence: 99%